Shaping a Sustainable Future: How Energy Consumption and Carbon Emissions Drive Low-Carbon Development - Siregar, Enni Sari (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: The study examines the impact of deforestation, energy use, transportation, and industrialization in North Sumatra from 1991 to 2021 on low-carbon development. It aims to understand environmental change drivers and propose strategies to mitigate their negative effects on development.Research Objectives: This research aims to explore the relationship between deforestation, energy consumption, land transportation, and industrialization as factors influencing low-carbon development.Research Methods: The study examines factors influencing low-carbon development in North Sumatra from 1991 to 2021, including energy consumption, land transportation, industrialization, and deforestation, influenced by population density and property rights.Empirical Results: The study reveals that deforestation, energy consumption, land transportation, and industrialization significantly impact low-carbon development in North Sumatra, with population density positively influencing deforestation.Implications: The research suggests that the government should implement policies to reduce deforestation, increase public transportation usage, and promote electric vehicles to achieve low-carbon development, promote efficient energy consumption, and encourage environmentally friendly technological innovation.JEL Classification: F21, F43, G18, H21, R23How to Cite:Siregar, E. S. (2025). Shaping a Sustainable Future: How Energy Consumption and Carbon Emission Drive Low-Carbon Development. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 93-110. https://doi.org/10.15408/sjie.v14i1.44779.